2018
DOI: 10.1002/oby.22262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self‐Conditioning Techniques (Self‐Hypnosis) in Promoting Weight Loss in Patients with Severe Obesity: A Randomized Controlled Trial

Abstract: Self-hypnosis was not associated with differences in weight change but was associated with improved satiety, QoL, and inflammation. Indeed, habitual hypnosis users showed a greater weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
0
18
0
4
Order By: Relevance
“…According to one RCT study on 120 participants with BMI ranges from 35 to 50 kg/m 2 , the addition of hypnotherapy to conventional lifestyle modification leads to a relatively small reduction in body weight. 18 However, those practicing self-hypnosis more than once per day showing greater weight loss and improved dietary intake after follow-up for 12 months (P < 0.001). At present, it is still unclear whether hypnotherapy is effective for reducing body weight because of limited research available.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…According to one RCT study on 120 participants with BMI ranges from 35 to 50 kg/m 2 , the addition of hypnotherapy to conventional lifestyle modification leads to a relatively small reduction in body weight. 18 However, those practicing self-hypnosis more than once per day showing greater weight loss and improved dietary intake after follow-up for 12 months (P < 0.001). At present, it is still unclear whether hypnotherapy is effective for reducing body weight because of limited research available.…”
Section: Resultsmentioning
confidence: 93%
“…In most studies, the participants were asked to follow a low-calorie diet and exercise regularly. 11 , 13 , 15 , 18 , 19 Five studies entailed a non-dieting approach in which participants required to maintain their dietary habits 14 , 16 , 17 , 20 , 21 and one study instructed participants to perform exercise moderately without dietary restrictions. 12 …”
Section: Resultsmentioning
confidence: 99%
“…In the self-hypnosis arm, a significant improvement in quality of life, satiety, and inflammation occurred with respect to controls with standard care, without a significant difference in weight loss (−6.5-kg intervention group, n =44 patients; −5.6-kg control group, n =42 patients; p =0.79). Indeed, within the intervention group, habitual hypnosis users showed a greater weight loss than those who practiced self-hypnosis less frequently (−9.6 kg, ≥ once per day; −7.5 kg <once per day; +0.2 rarely or none; p =0.001) [ 48 ]. The same research group reported an acute effect on the brain peptides involved in the hunger/satiety regulation after a hypnosis-induced hallucinated meal in highly hypnotizable individuals, thus suggesting the potential role of hypnosis on central appetite modulation [ 49 •].…”
Section: Hypnosismentioning
confidence: 99%
“…In conclusion, 11 randomized trials about the effect of hypnosis as an adjunctive strategy to lose weight were published; out of them, 9 [ 42 44 , 48 , 50 – 54 ] reported overall beneficial effects, even if mild or moderate and more evident after a longer follow-up [ 42 , 44 , 50 , 51 , 53 ], while only 2 [ 55 , 56 ] failed to find any benefits.…”
Section: Hypnosismentioning
confidence: 99%
See 1 more Smart Citation